Antegrade Hybrid Chimney TEVAR Endograft in a Patient with Blunt Aortic Injury: A Challenging Case with Technical Success but Unfavorable Result. (13th April 2021) - Eforakopoulos, Fotios; Giovani, Maria; Zampakis, Petros; Kalogeropoulou, Christina; Fligou, Fotini; Charoulis, Nikolaos; Koletsis, Efstratios; Dougenis, Dimitrios
Abstract : Thoracic Endovascular Aortic Repair (TEVAR) has modified aortic medicine, particularly in patients with traumatic aortic injury (TAI). Conventional repair of TAI in the aortic arch is technically demanding as it requires cardiopulmonary bypass and deep hypothermic arrest with still a significant number of complications. Despite recent improvements in endovascular techniques, many patients have been excluded from endovascular repair due to unfavorable anatomy. To increase the feasibility of endovascular repair, adjunctive open extra-anatomical bypasses may be required to provide an adequate proximal landing zone. Several methods, for instance, chimney technique, hybrid technique, and fenestrated or branched stent-grafts, have been proposed as options to preserve the supra-aortic branches, each with its own advantages and disadvantages. We herein present a patient with complex anatomical features and blunt aortic injury, who underwent antegrade chimney stent-graft deployment through the ascending aorta, not otherwise amenable to standard retrograde delivery because of severe peripheral artery disease. The remarkable aspect, in this case, is that both stents were placed antegrade, through the ascending aorta.